"Safety and healthcare provision in space analogs". (September 2021) - Posselt, Bonnie N.; Velho, Rochelle; O'Griofa, Marc; Shepanek, Marc; Golemis, Adrianos; Gifford, Sheyna E.
Abstract: Space agencies use terrestrial-based analog missions to reduce risk and cost of spaceflight operations. This paper explains how research simulations differ from more traditional spaceflight analogs, and describes medical mishaps that may occur. Suggested paths to improved safety standards will better prepare health and safety officers to address healthcare gaps. Highlights: Analog space missions use terrestrial environments to simulate aspects of real space. They vary significantly in fidelity, funding, resources, and organization. A safety focused risk assessment should be conducted regardless of analog type. The roles and responsibilities of health and safety officers are many and diverse. Reporting significant adverse events is encouraged.